Reflections on oral tradition in the classroom (2022)
This article presents a reflection on the state of the art of oral tradition. The study is a documentary, interpretative design. Initially, the characteristics of the methodology are shown, followed by a discussion of the categories: oral tradition and education; cultural globalization and social transformations in education; and oral tradition and technology, and finally, the conclusions. Among the most important considerations are the importance of oral tradition in the classroom for its multiple benefits, relating orality and technology as a strategy of the globalized world and using transmedia narrative as a tool to strengthen orality.